Lower extremity muscle activity during reactive balance differs between adults with chronic traumatic brain injury and controls - Cesar, Guilherme M.; Buster, Thad W.; Burnfield, Judith M. (Frontiers in Neurology, 2024)
Background: Control of reac ve balance is key to achieving safe independent walking and engagement in life ac vi es. A er trauma c brain injury (TBI), motor impairments and mobility challenges are persistent sequela. To date, no studies have explored muscle ac vity of individuals with chronic TBI during a task that requires reac ve control of balance.To inves gate lower extremity muscle ac vity during a reac ve balance test performed by adults with chronic severe TBI and matched controls. We hypothesized that abnormal ac vity of lower extremity muscles would be related with poorer reac ve balance performance. Also, we performed an exploratory analysis for those with TBI inves ga ng the impact of unilateral versus bilateral lower extremity involvement in the control of reac ve balance.Methods: Ten adults with chronic severe TBI who were independent community ambulators and ten matched controls performed the computerized reac ve balance test (Propriotest ® ) while lower extremity muscle ac vity was recorded. Electromyographic (EMG) ac vity was contrasted (Mann-Whitney U Test) between groups across each 10-second epoch of the 120second test. Addi onally, test scores were correlated (Spearman) with lower extremity composite EMG ac vity to dis nguish muscle ac vity pa erns related with reac ve balance performance. Lastly, reac ve balance test scores were correlated with reac ve balance test scores and clinical func onal measures only for the TBI group.Results: Although the TBI group exhibited greater EMG ac vity across the en re test compared with the control group, significant differences were not observed. Greater composite EMG ac vity correlated significantly with poorer reac ve balance performance across most of the 10second windows of the test.Greater muscle ac vity exhibited during the reac ve balance test by individuals with chronic severe TBI compared to those without disabili es, par cularly at small unexpected perturba ons, highlights the greater physiologic effort required to control reac ve balance even a er independent ambula on is achieved.